Perception of Accounting Students Over Professional Certification Exam: Case Study on Accounting Studies of Vocational UI - Anggraeni, B D; Aulia, S; Kartikasari, D (KnE Social Sciences, 2018)
Vocational education is an applied education in which students are required to have professional certification. This research is to delve deeper into student perceptions on professional certification exams in accounting and factors that influence students’ decision to follow professional certification. This study used a questionnaire that was distributed to accounting students and collected as many as 157 questionnaires for the purposes of this study. The study used regression analysis and descriptive analysis. The results of this research aims to study the program to better play the role of faculty and university management to further influence and motivate students to obtain a professional degree. Students can have a positive impact in the workplace. This study is confined to the accounting program of the students and the sample data used has not been evenly distributed at every level. Keywords: accounting, professional certification, vocational student